Ethnography, visual narratives and learning ecologies. The 'Universidad Rural Paulo Freire' case. - Cortés-González, Pablo; Rivas-Flores, José Ignacio; Leite-Méndez, Analía Elizabeth; García-López, Marcial (My University, 2017)
In this paper, we present some of the results of the R&D Project called "Ecologies of learning in multiple contexts: analysis of expanded education projects and citizenship configurations" funded by Minister of Economy and Competitiveness (Spain). The interest of this project arises after considering that much of the individual and organizational learnings have been turning invisible in different educational spaces. Therefore, our purpose is to study the different socio-educational mechanisms that individuals and organizations put into play in different scenarios: schools, asociations, virtual academical contexts, etc. On this ocassion, we present some of the methodological issues and results of a specific case: "La Universidad Rural Paulo Freire de la Serranía de Ronda" (onwards URPF), a rural socio-educative organization. The ethnography is being developed in Benalauría (Ronda mountain range). This organization is focused in the recovery of traditional learnings that people used to have around the rural world. It is settled in a critical perspective that connects their educational actions under the approaches of sustainability, dignity, feminism, etc. The general objectives we consider for this project are the following: - To know life style of people in Benalauría context. - To understand the configuration of URPF group and its impact in the territory. - To promote learning communities of practice with other organizations. As specific objectives, we emphasize: - To review the conceptual frameworks those allow us to understand the practices of invisible learning in this experience. - To generate visual narratives those evidence the work and identity features of the URPF. - To analyse the life stories of the people who are part of this experience (as well as the collective story), for the understanding of socio-educational action in rural contexts through dialogue of knowledge, generation of democratic practices and collaborative participation. - To generate spaces for dialogue with other organizations, groups and people for the creation of networks and learning communities.
Keywords: Enseñanza - Congresos; Etnografía; Educación; Ámbito rural; Narrativas